PENANGANAN SENGKETA PERDAGANGAN INTERNASIONAL MELALUI WTO (WORLD TRADE ORGANIZATION) - Imawan Dicky Prasudhi (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2007)
WTO (World Trade Organization) is negotiation forum to discuss the commerce problem that arising out among contracting parties - Section III : 3 Agreement of Establishing the Multilateral Trade Organization. WTO have also made an arrangement concerning of dispute settlement which arranged in Annex 2